Potential reversible and high-capacity hydrogen storage medium: Li-decorated B3S monolayers. (December 2021) - Yong, Yongliang; Hu, Song; Zhao, Zijia; Gao, Ruilin; Cui, Hongling; Lv, Zhenlong
Abstract: The potential application of the B3 S monolayer with and without Li decorated as hydrogen storage materials (HSMs) were studied using DFT calculations. We found that the interactions between H2 molecule and the pure B3 S monolayer is too tiny to meet the requirements of optimal HSMs. The large binding energy (3.00–3.30 eV) of Li atoms on the B3 S monolayer effectively hinders Li clustering. The adsorption energy per H2 for H2 molecules on the Li-decorated B3 S monolayer is as moderate as between 0.167 and 0.208 eV, and the electrostatic nature of the interactions between H2 and Li-decorated monolayers is found. The Li-decorated B3 S monolayers have high gravimetric and volumetric capacity of 7.7 wt% and 94.8 g/L, respectively. The desorption temperature indicates that the Li-decorated B3 S monolayers as HSMs have high reversibility over the temperature of 224 K, and AIMD simulations show that H2 molecules have no kinetic hindrance for desorption. Therefore, the Li-decorated B3 S monolayers are reversible and high capacity materials for hydrogen storage meeting the targets of U.S. DOE. Graphical Abstract: ga1 Highlights: Hydrogen storage properties of Li-decorated B3 S monolayer was studied using DFT method. Li-decorated B3 S monolayer stores 7.7 wt% H2 with ideal adsorption energy. .Interactions between H2 molecules and Li-decorated B3 S monolayer are electrostatic nature. Desorption temperature and AIMD simulation verify the reversibility of H2 storage.